. HUBUNGAN TINGKAT PENDIDIKAN DAN LAMA KERJA PERAWAT DENGAN KINERJA PERAWAT DI RSU PANDAN ARANG KABUPATEN BOYOLALI - Faizin, Ahmad; Ambarwati, Winarsih Nur (Universitas Muhammadiyah Surakarta, 2008)
Background: this research background was the problem of quality of treatment service at hospital, representing service form which was passed by client by an team of multi discipline is including care team. Team of treatment service give the service to client as according to confidence of standard and profession specified. Target of: target of this research is to know correlation between the education and long of working the nurse to The performance nurse on Pandan Arang Hospital in Boyolali. This Research represent the research with the analytic descriptive method with the approach of cross sectional study. Population in this research is nurse at Pandan Arang Hospital in Boyolali, calculated are 107 nurses. Sample technic was population research. Result of calculation test the hypothesis use the statistical test of Chi Square by means of assist the program of SPSS version 13. Concluded: (1). There is relation between nurse education at Nurse on Pandan Arang Hospital in Boyolali, and ( 2). There is relation between long of working the nurse to nurse performance at nurse on Pandan Arang Hospital in Boyolali. Suggested that a nurse improve the caring performance for the patient hospitalization with by following workshop, training or continue the school to higher level and expected a nurse to increase its performance a nurse which have status part-time its contract so that can work longer in Pandan Arang Hospital in Boyolali.